1995
DOI: 10.1002/aoc.590090810
|View full text |Cite
|
Sign up to set email alerts
|

A new procedure for the speciation of mercury in water based on the transformation of mercury (II) and methylmercury (II) into stable acetylides followed by HPLC analysis

Abstract: Conversion of mercury(I1) and methylmercury(I1)species dissolved in water into di(pheny1-ethyny1)mercury and methyl(phenylethyny1) mercury takes place in satisfactory yield under alkaline conditions by stirring the aqueous solution with phenylacetylene at room temperature. Mercury speciation is simply obtained by HPLC analysis of the two organometallic species. The presence of heavy metals such as copper(II), zinc-(JI), cadmium(I1) and lead(11) in concentrations 10 000 times higher than mercury is tolerated, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We have recently reported that the reaction of CH 3 HgCl ( 1 ) with phenylacetylene in alkaline aqueous solution affords CH 3 HgC⋮CPh. The reaction is fast, and a new method of analysis of 1 was proposed, based on extraction of CH 3 HgC⋮CPh followed by HPLC separation and UV detection . Here we wish to broaden the scope of the reaction, showing that the reaction of 1 with 1-alkynes (i) is general, since other aromatic and heteroaromatic 1-alkynes can be used, and (ii) represents a very simple way to link a fluorescent label to 1 by exploiting properly tailored alkynes.…”
mentioning
confidence: 99%
“…We have recently reported that the reaction of CH 3 HgCl ( 1 ) with phenylacetylene in alkaline aqueous solution affords CH 3 HgC⋮CPh. The reaction is fast, and a new method of analysis of 1 was proposed, based on extraction of CH 3 HgC⋮CPh followed by HPLC separation and UV detection . Here we wish to broaden the scope of the reaction, showing that the reaction of 1 with 1-alkynes (i) is general, since other aromatic and heteroaromatic 1-alkynes can be used, and (ii) represents a very simple way to link a fluorescent label to 1 by exploiting properly tailored alkynes.…”
mentioning
confidence: 99%
“…conditions is known to afford the corresponding methylmercury acetylides [19], in analogy to the known chemistry of Hg(II) which affords diacetylides under the same reaction conditions [4]. In addition, we previously demonstrated that the reaction of Hg(II) and MMHg with phenylacetylene in water is not affected by the contemporary presence of Cu(II), Zn(II), Cd(II) and Pb(II) in concentrations 10 4 higher than mercury [19b].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, different microextraction techniques coupled with atomic absorption spectrometry have been used for the determination of Hg(II) [15][16][17]; however, very few works are found in the literature in which the speciation of mercury and its subsequent quantification are carried out [18]. Moreover, the analysis of MeHg in water samples is usually carried out using chromatographic techniques, although a derivatizing treatment of the sample is required [19,20]. Recently, the use of novel, hybrid sorption nanomaterials such as graphene oxide functionalized with ionic liquids (IL), and graphene-nickel functionalized with IL, have allowed the determination of Hg(II), MeHg and phenyl mercury (PhHg) without using chromatographic systems [21], although the separation of these materials from the analysis medium is difficult to complete.…”
Section: Introductionmentioning
confidence: 99%